TRENDS AND PATTERNS IN ONLINE PURCHASE DECISION RESEARCH A LITERATURE REVIEW AND BIBLIOMETRIC ANALYSIS - Sulistyowati, Tussi (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2024)
Abstract : The internet has transformed the way consumers make purchase decisions, and with the increasing popularity of e-commerce, it has become vital to understand the factors that influence online purchase decisions. The COVID-19 pandemic has further accelerated the shift towards online shopping, making it even more crucial to understand the online purchase decision-making process. This bibliometric review examines 95 articles on the keyword "online purchase decision" from Scopus journals generated by Publish or Perish on April 25th, 2023, to identify the most influential authors and trends in this field from 2002 to 2023. The study reveals a steady rise in publications on this subject over time, with a significant surge in recent times. S. Yoon emerged as the most cited author in this field, followed by H.W. Kim and N. Hu. "Decision Support Systems" is the most productive journal in this field, and M. Ramesh is the most prolific author. The research variables have similarities and differences in focus and approach. For instance, trust, price, reviews, website characteristics, and the influence of social media are the focuses in these studies. The studies differ in their approaches and focuses. For example, (Yoon, 2002) examines the antecedents and consequences of trust, (Kim et al., 2012) compares price and trust, (Hu et al., 2014) analyzes online review sentiment, and (Luo et al., 2012) investigates the impact of website characteristics. There are also differences in the scope of the research, including cross-cultural approaches, the teenage market, gender, and potential customers vs. repeat customers. The findings of this study provide valuable insights into the key trends and patterns in online purchase decision-making research, which can inform marketing strategies and improve online salesKeyword : Keputusan Pembelian Online, Analisis Bibliometrik, Perilaku Konsumen